Chemical, isotopic and gas composition of the first-year sea ice in 2013-2015 from the data of cores taken at the BARNEO drifting stations - A. I. Kizyakov; I. D. Streletskaya; A. V. Savenko; I. A. Kraynyukova; I. V. Tokarev (Ice and Snow, 2019)
As a result of the work performed at the BARNEO drifting stations (2013-2015 in the polar region of the Arctic ocean), a comprehensive testing was carried out and new data were obtained on the structure of one-year sea ice, its salinity, the distribution of ions of water-soluble salts, and the content of isotopes δ2H and δ18O within the ice thickness and snow falling on the ice surface. The composition of gas inclusions in the ice was also determined. The distribution of electrical conductivity across the ice thickness, determined by analysis of the cores with a length of 175-178 cm, is typical for such ice - it decreases from top to bottom with two maxima on the lower and upper boundaries of the ice. This is typical characteristic of the first-year sea-ice. Snow cover is characterized by a significant increase in electrical conductivity at the contact with the underlying ice. The chemical composition of the investigated ice-cores and the ratio between its components are similar to the composition of the sea water, although the concentrations of all components are lower than in the initial solution. The composition of gas inclusions in the ice does closely correspond to the atmospheric air, and it practically does not change in depth. The isotopic composition in the cores becomes heavier towards the bottom of the ice. This allows conclusion of a gradual decrease in the contribution of water with a light isotopic composition. The change in the isotopic composition along the ice depth, with the separation of zones with more light isotopes, reflects the changing temperature conditions of ice accumulation (with low isotopic fractionation at rapid freezing under the large temperature gradient) and regional features of the isotopic composition of sea waters in which the ice drift takes place. Salinization of the snow horizon lying on the ice surface provides a possibility of the sea salt transportation not only from surface of open water, but also from the surface of sea ice. This may be used for paleogeographic ...